Analysis of Social Well-being Parameters in Russia (on the Example of the Remote Siberian Region); Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Bulatova T. A. Tatjyana Alekseevna (2016, 2016)
Title screen